Digital Accounting: A Bibliometric Analysis of Research Trends and Thematic Evolution (2000–2026) - Loso Judijanto; ABDUL MUIZ (Westscience Press, 2026)
This study aims to analyze the development, intellectual structure, and thematic evolution of digital accounting research from 2000 to 2026 using a bibliometric approach. Data were collected from the Scopus database and analyzed using VOSviewer to examine publication trends, keyword co-occurrence, and thematic progression over time. The results reveal a significant growth in digital accounting research, driven by the increasing integration of advanced technologies such as artificial intelligence, blockchain, big data, and machine learning into accounting practices. The co-occurrence analysis identifies several major research clusters, including digital transformation in accounting, emerging technologies, data analytics, and governance-related issues. Overlay visualization indicates a clear evolution from early themes of digitalization and accounting information systems toward more recent topics such as intelligent systems, predictive analytics, and sustainability. Furthermore, density analysis highlights digital storage, artificial intelligence, and digital transformation as the most central and influential themes within the field. These findings suggest that digital accounting has evolved into an interdisciplinary domain that integrates technology, data infrastructure, and strategic decision-making. This study contributes to the literature by providing a comprehensive mapping of the field and offering insights into emerging research directions, including AI ethics, blockchain-based reporting, and sustainability-oriented accounting systems.